The Ethics of Corporate Social Responsibility and Philanthropic Venturesl - Wulfson, Myrna (Journal of business ethics, 2001)
Andrew Carnegie popularized the principles of charity and stewardship in 1899 when he published The Gospel of Wealth. At the time, Carnegie's ideas were the exception rather than the rule. He believed that businesses and wealthy individuals were the caretakers or stewards of their property holding it in trust for the benefit of society as a whole., One of the most visible ways a business can help a community is through corporate philanthropy. While the courts have ruled that charitable contributions fall within the legal and fiduciary powers of the corporation's policymakers, some critics have argued that corporate managers have no right to give away company money that does not belong to them and any income earned by the company should be either reinvested in the company or distributed to the stockholders.